Strategic Development of Transportation Demand Management in Jordan - Basim Jrew; Majed Msallam; Mona Momani (Civil Engineering Journal, 2019)
The urban population growth and increase in a number of vehicles have affected the travel demand on Jordan Streets. The study aims to apply the Transportation Demand Management (TDM) policies to reduce the traffic flow in urban areas and improve the Level of Service (LOS). A group of a combination between TDM and Transportation System Management (TSM) strategies have been conducted, when TDM strategies were not successful to improve LOS. TSM concept refers to any group of actions that increase the capacity of roads network. Synchro 8 software was used to analyse the intersection conditions as important point, connecting two main arterial street in Amman area. A significant reduction in delay and fuel consumption was measured, but there was no real enhancement in LOS. The LOS was improved, when traffic demand was reduced by 20% and capacity was increased with 6 lanes on each approach for the existing conditions. The percentage of saving in fuel consumption and delay was observed to be around 64% and 63%, respectively for the next 5 years.